2009
DOI: 10.3382/ps.2008-00418
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle changes in bone mineralization and bone size traits of commercial broilers

Abstract: Life cycle changes in bone mineralization and bone size traits of the tibia and humerus were evaluated in commercial male and female broilers using dual-energy x-ray absorptiometry (DEXA). Experiment 1 evaluated weekly changes in bone traits from 2 to 7 wk of age, whereas experiment 2 compared the bone traits of 4 strains of commercial meat-type chickens from 4 to 8 wk of age. Birds were restrained without anesthesia, and the humerus and tibia were scanned in vivo. After each scan, individual BW was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…This result is consistent with that reported by Barreiro et al (2009). Talaty et al (2009) also found that chicks exhibited the greatest tibia mineral density at 28 d of age. Similarly to ash content, metatarsus Ca content linearly increased with age.…”
Section: Bone Ca Contentsupporting
confidence: 83%
“…This result is consistent with that reported by Barreiro et al (2009). Talaty et al (2009) also found that chicks exhibited the greatest tibia mineral density at 28 d of age. Similarly to ash content, metatarsus Ca content linearly increased with age.…”
Section: Bone Ca Contentsupporting
confidence: 83%
“…A similar observation was reported by McDevitt et al (2006), who notes that dry bone weight and mineral content per unit length of modern broiler strains increase in direct proportion to the increase in BW. In contrast, inadequate dietary sources of Ca result in blood hypocalcaemia, leading to reduced bone strength and mineralization (Talaty et al, 2009a).…”
Section: Resultsmentioning
confidence: 99%
“…A high molar Ca : phytate ratio in the diet may lead to the formation of extremely insoluble Ca-phytate complexes under intestinal conditions, making the phytate molecule inaccessible to the phytase enzyme (Kornegay, 1999). Inadequate dietary sources of calcium result in blood hypocalcaemia, leading to reduced bone strength and mineralization (Talaty et al, 2009a). Typically, supplementation of the phytase enzyme in grain-based poultry diets has become common practice to increase phosphorus bioavailability by 25% -50%, reduce phosphorus excretion by 15% -40%, and ensure proper growth and bone development (Harter-Dennis, 1999;Onyango et al, 2006;Coon & Manangi, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional intensive production conditions do not allow sufficient exercise and typically present poor hygiene, resulting in leg weakness and skin infections (Bessei, 2006;Talaty et al, 2009). It has been demonstrated that the bones of fast growing meat-type chickens are often abnormally developed, and present high porosity and much lower density than those of slow-growing broilers (Bennett, 2008;Williams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%